(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the theoretical aspects of the study of reproductive health: the essence of the concept, the factors that negatively affect reproductive health, the current state of reproductive health of students, the means to improve it, and the social consequences. Research on the sociological study of the reproductive health of students of Gulistan State University was conducted. The theoretical conclusions of the study were aimed at shaping the reproductive culture of young people, which allowed developing a number of proposals and recommendations on various social services that can be provided by higher education institutions.